2021
DOI: 10.1017/jog.2021.118
|View full text |Cite
|
Sign up to set email alerts
|

Crack propagation speeds in weak snowpack layers

Abstract: For the release of a slab avalanche, crack propagation within a weak snowpack layer below a cohesive snow slab is required. As crack speed measurements can give insight into underlying processes, we analysed three crack propagation events that occurred in similar snowpacks and covered all scales relevant for avalanche release. For the largest scale, up to 400 m, we estimated crack speed from an avalanche movie; for scales between 5 and 25 m, we used accelerometers placed on the snow surface and for scales belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…• On the one hand, for short propagation distances, typically below 2 m, the failure in the weak layer occurs as a so called mixed-mode anticrack (Heierli et al, 2008), in line with field measurements (Bergfeld et al, 2022; as well as recent numerical experiments using the DEM (Gaume, van Herwijnen, et al (2015) and Bobillier et al (2021)). The anticrack mechanism, originally introduced to explain deep earthquakes (Fletcher & Pollard, 1981) refers to a mode of compressive fracture driven by the volumetric collapse of the highly porous weak layer, which leads to the closure of crack faces and to the onset of frictional contact (Gaume et al, 2018).…”
supporting
confidence: 79%
“…• On the one hand, for short propagation distances, typically below 2 m, the failure in the weak layer occurs as a so called mixed-mode anticrack (Heierli et al, 2008), in line with field measurements (Bergfeld et al, 2022; as well as recent numerical experiments using the DEM (Gaume, van Herwijnen, et al (2015) and Bobillier et al (2021)). The anticrack mechanism, originally introduced to explain deep earthquakes (Fletcher & Pollard, 1981) refers to a mode of compressive fracture driven by the volumetric collapse of the highly porous weak layer, which leads to the closure of crack faces and to the onset of frictional contact (Gaume et al, 2018).…”
supporting
confidence: 79%
“…12). Interestingly, this simulation shows a race between crack propagation in the weak layer and slab fractures, leading to lateral en-echelon failures, a process often reported in the field (Bergfeld et al, 2022). The overall shape differs from the pictures in Fig.…”
Section: Discussionmentioning
confidence: 66%
“…This is why in our case, we have a smooth increase of the speed towards the longitudinal wave speed c P . In 3D simulations, a daughter supershear crack nucleates ahead of the main fracture with a speed which continuously increases towards c P , while crossing the forbidden region between c R and c S (Gaume et al, 2019;Bergfeld et al, 2022;Bizzarri & Das, 2012). We obviously cannot reproduce the discontinuity reported in 3D simulations, but the temporal evolution of the supershear crack speed is in line with the latter 3D simulation.…”
Section: Discussionmentioning
confidence: 67%
“…However, the typically 2-3 m long PST experiments are rather small tests, pos-sibly not representative of slope scale crack propagation in avalanches. While the one-dimensionality of crack propagation along PST columns seems not be altering crack propagation speed (Bergfeld et al, 2022), crack propagation in PSTs of typical size is affected by edge effects Bair et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Based on videos of avalanches, Hamre et al (2014) reported widely varying crack speed estimates ranging from 18 to 428 m s −1 . Bergfeld et al (2022) improved the methodology and estimated crack speeds by evaluating 14 crack paths in an avalanche video recording, resulting in crack speeds between 23 and 44 m s −1 (mean: 36 ± 6 m s −1 ) covering distances from 26 to 440 m. In addition to these experimental studies, Trottet et al (2022) performed numerical simulations based on the material point method (Gaume et al, 2018b) and reported the existence of a transition from sub-Rayleigh anticrack to supershear crack propagation. While sub-Rayleigh anticrack propagation can explain crack speeds below 100 m s −1 , the transition to supershear crack propagation (a crack propagating faster than the shear wave speed in the slab) potentially also explains the high crack speeds reported by Hamre et al (2014).…”
Section: Introductionmentioning
confidence: 99%